ISRAEL S KIBBUTZS AS A SUI GENERIS COOPERATIVE MODEL (Third Sector Social Economic Review, 2016)
In this study we deal with the kibbutz which means “union” or “society” in Hebrew language, functions as collective farms. First of all we start with the historical development of kibbutz, then ideological structure and economical mode of production, after that we try to explain the administrative and organizational structure of kibbutz. The aim of this paper is to show the kibbutz’s structure and function which has been playing a key role in the process of the demolition of Ottoman Empire, the seizure of Great Britain rule in Middle East and finally the establishment of Israel State.
Keywords: Kibbutz; Collective Farming; Cooperative Model; Israel; Jewish Nationalism